Interventions Implemented for the Prevention and/or Management of Childhood Traumatic Grief in Sub-Saharan Africa - Taggart, Holly (2012)
Background - Childhood traumatic grief is caused when a significant person in a child’s life dies, either unexpectedly or anticipated, under circumstances that they perceive to be traumatic. This can leave a child unable to return to the same level of physical and emotional functioning prior to the death occurring. In Sub-Saharan Africa, there is an increased risk of childhood traumatic grief due to a high prevalence of orphanhood, environmental stressors, stigma and abuse. This is considered to have detrimental effects upon mental health, potentially resulting in anxiety, depression and post-traumatic stress disorder. An absence of mental health services and policies within Sub-Saharan Africa is apparent. This makes childhood traumatic grief a topic of global importance within research as well as within service and policy development. Aim - Identify interventions implemented for the prevention and/or management of childhood traumatic grief in Sub-Saharan Africa with the purpose of identifying best practices and sharing information. Methodology and Methods - A modified systematic review was conducted and the following sources searched: AMED, ASSIA, CINAHL EMBASE, MEDLINE, PsycINFO, HOPE-HIV, OVC, Population Council, Save the Children, THET, UNAIDS, UNICEF and WHO. Predetermined inclusion/exclusion criteria identified eleven studies for inclusion within the review. Key Findings - Interventions identified to prevent and/or manage traumatic grief included narrative exposure therapy, psychotherapy, mentoring, peer group support, psychosocial support, a grief and loss therapy session and memory boxes. Conclusions and Recommendations - Interventions addressed the psychological, social, psychosocial and emotional needs of young people who were experiencing, or were at risk of experiencing, traumatic grief. Further research and dissemination of findings was recommended. Limitations - A ‘full’ systematic review could not be implemented due to time and financial constraints. Researcher bias was also possible due to a single researcher conducting the review. Included studies were less academically rigorous than usually expected within a modified systematic review.